Manajemen Kurikulum Berbasis Pesantren untuk Membentuk Karakter Siswa di SMP Al-Azhar Menganti Gresik - Syarifuddin Hidayatulloh (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
The results of this study show that curriculum planning based on pesantren is carried out by involving several parties both from sekolah and from pesantren, namely education bureaus and leadership bureaus. At this stage of planning, the two bureaus designed the books that would be made referenced and studied in the Madrasa. Two methodologies are used in the implementation of learning: conventional methods such as bandongan and, when necessary, active learning techniques. Evaluation of the pesantren-based curriculum focuses on students' morality and discipline both at home and in the educational environment.